Achoccha—Cyclanthera pedata L. - James M. Stephens (EDIS)
This document provides an overview of Achoccha (Cyclanthera pedata), a trailing vine known for its segmented leaves and hollow cucumber-like fruits. It details the plant's propagation, soil preparation, and fruit production, noting its limited fruiting in Florida. Original publication date April 1994.